An investigation of the relationship between intercultural sensitivity and compassion in nurses. (March 2018) - Arli, Senay Karadag; Bakan, Ayse Berivan
Abstract: This study aims to investigate the relationship between intercultural sensitivity and compassion levels in nurses. A cross-sectional relational study was conducted. It was conducted with the participation of 134 volunteer nurses who worked in Family Health Centers (FHCs) and the State Hospital in a city located in the eastern part of Turkey between April and June, 2017. Data were collected through the Socio-Demographic Characteristics Form, the Intercultural Sensitivity Scale, and the Compassion Scale. A significant, positive relationship was found between the Intercultural Sensitivity Scale and Compassion Scale mean scores (p < 0.001). It is recommended that moving nursing profession to a better position in the globalised world and providing quality patient care could be achieved through trainings on compassion and intercultural sensitivity given in undergraduate or postgraduate education programs. Concepts of intercultural sensitivity and compassion were found to affect each other directly.